AI vs. Human Doctors: Which is More Accurate in the Digital Health Era? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The question of whether Artificial Intelligence AI can outperform human physicians in diagnostic accuracy sits at the heart of the digital health revolution....
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care